AB0088 Deficient Autophagy Induces Premature Senescence in Aging and Osteoarthritis. (9th June 2015) - Carames, B.; Lόpez de Figueroa, P.; Calamia, V.; Ribeiro, M.; Blanco, F.J.
Abstract : Background: Osteoarthritis (OA) is characterized by insufficient extracellular matrix synthesis and articular cartilage degradation. Autophagy is essential to maintain chondrocyte homeostasis by regulating the intracellular macromolecule and organelle turnover (1). Previous findings indicated that autophagy is defective in Aging and OA articular cartilage (1, 2), but the specific target/-s that regulates this mechanism and affect cartilage integrity are still unknown. Objectives: The objective of study is to identify relevant targets regulating autophagy in Aging and OA by proteomics. Methods: Primary human chondrocytes from human donors were transfected with siRNA for Atg5 (100 nM, 72 hours), a key autophagy marker, to block the autophagy pathway. To identify the key proteins responding to defective autophagy, we performed a quantitative proteomics analysis of autophagy-deficient human chondrocytes using labeling iTRAQ (isobaric tags for relative and absolute quantitation) coupled with on-line 2D LC/MS/MS. Protein identification and quantification were performed using Protein Pilot Software v4.0 (ABSciex). Each MS/MS spectrum was searched in the Uniprot/Swissprot database for Homo sapiens . To confirm the candidate targets identified by the proteomic screening, inmortalized human chondrocytes (Tc28a2), human cartilage from healthy, aged and osteoarthritis human patients and mouse knee joints from young and old mice were employed to perform Western Blot and Histology analysis, respectively. The candidate targets were: Atg5 and LC3 for constitutive autophagy, p62, as a defective autophagy marker, Lamin A/C as an aging marker. Results: From the total of 599 proteins found, 21 were significantly altered (p<0.05) in at least two donors from a total number of three. However, Lamin A/C, a nuclear protein implicated in premature cell senescence, was significantly upregulated in all the donors (p<0.05). To validate these results, TC28a2 human chondrocytes were transfected with siAtg5. Then, the expression of Atg5, LC3, p62, and Lamin A/C was evaluated. The results indicated a reduction in autophagy expression, accompanied with an increase in aging marker expression. Importantly, in human cartilage from both aged and OA patients, autophagy markers were significantly downregulated and Lamin A/C expression was upregulated, compared to healthy cartilage. Furthermore, articular cartilage from young mice (4 months old) and old mice (28 months old) was studied, suggesting that autophagy loss-of-function is correlated with premature senescence in articular cartilage. Conclusions: Proteomics analysis of joint cells and tissue has revealed features of premature senescence when autophagy is disrupted in chondrocytes and cartilage. Lamin A/C, was identified as candidate target for regulating cartilage function in situations of defective autophagy, including aging and OA. These results support the hypothesis that autophagy is decreased with aging, and represents a key mechanism in the development of cartilage degradation. References: Caramés B., et al., Arthritis Rheum, 2010 Caramés B., et al, Arthritis Rheum, 2015 (In press) Acknowledgements: This study was supported by Instituto de Salud Carlos III- Ministerio de Economía y Competitividad, Spain-CP11/00095. Disclosure of Interest: None declared